Teaching Social Issues in Use of Medicines to Pharmacy Students - Shankar, Pathiyil Ravi; Palaian, Subish (Journal of Pharmacy Practice and Community Medicine)
Introduction: Pharmacists can help people understand, manage and use their medications appropriately. The subject of social pharmacy is gaining in importance in many countries. In South Asia pharmacy education concentrates on technical drug related aspects. Pokhara University conducts an undergraduate programme in Pharmacy. The students are trained in various aspects of Clinical Pharmacy at the Manipal Teaching Hospital (MTH). Methods: The authors conducted a session on ‘Social issues in use of medicines’ using case scenarios and role-plays. The students were divided into three small groups of 5 or 6 students each. Each group was given three case scenarios and analyzed and presented these using role-plays. The major issues covered were access to medicines/healthcare, aggressive pharmaceutical promotion, misconceptions about disease, brand versus generic medicines, drug regulation, ethical issues in clinical research, etc. The degree of agreement of the participants with a set of 15 statements was noted using a modified Likert-type scale. Free text comments about the session were invited. Results: A total of 31 students participated. The median (interquartile range) score was 61 (58-64). The maximum possible score was 75. The students enjoyed the session and felt it would be useful in their future career. Conclusion: The overall student opinion regarding the session was positive. We plan to continue the session in future.
Keywords: Case scenarios; Nepal; Role-plays; Social issues; Undergraduate pharmacy students